Volatile Compound Profiles of Indonesia's 'Cilembu' Sweet Potato (Ipomea batatas L. var. Rancing): Impact of Storage - Astuti, Rizki Maryam; Apriyantono, Anton; Cempaka, Laras; Adilah, Malikah (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Native to the west Java Region, Indonesia, ‘Cilembu’ sweet potatoes (Ipomea batatas L. var Rancing) is highly valued for its unique taste. However, the volatile compound profile of Cilembu sweet potato (CSP) has not been fully characterized. Therefore, this study aimed to analyze volatile compounds in CSP after conventional baking and storage, compared to Manohara sweet potato (MSP). Volatile compounds were analyzed using Gas Chromatography Mass Spectrometry (GCMS). The result showed that benzaldehyde was a key volatile compound in fresh CSP tubers. In comparison, MSP was dominated by terpenes as the main components, including α-gurjunene, methoxy-phenyl-oxime, and cymene. During storage, the sugar content in CSP surged due to starch hydrolysis, leading to the formation of Maillard reaction products, such as furfural, benzaldehyde, and 2-furan methanol, and these compounds contributed to the distinctive flavor of oven-baked CSP.